2008
DOI: 10.1007/s11596-008-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of RhoC siRNA on the invasiveness and proliferation of human cervical cancer cell line SiHa cells

Abstract: This study investigated the effect of RhoC GTPase on the proliferation and metastasis of cervical cancer cells, SiHa cells, in vitro. RhoC siRNA was introduced into SiHa cells to silence the RhoC gene. The mRNA and protein expression of RhoC, before and after RhoC siRNA transfection, was examined by RT-PCR and Western blotting, respectively. The proliferation and apoptosis of SiHa cells were examined by MTT assay and flow cytometry (FACS), respectively. Adhesive rate was evaluated by Matrigel adhesive assay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In accordance with its contribution to motility and invasion of several cancers (van Golen et al, 2000b;He et al, 2008), our data show that RhoC contributes to tumour progression by affecting invasion, anoikis resistance, tumour growth and angiogenesis in cervical carcinoma cell lines. We show that RhoC drives tumour progression by regulating invasion, metastasis, tumour growth and angiogenesis ( Figure 1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with its contribution to motility and invasion of several cancers (van Golen et al, 2000b;He et al, 2008), our data show that RhoC contributes to tumour progression by affecting invasion, anoikis resistance, tumour growth and angiogenesis in cervical carcinoma cell lines. We show that RhoC drives tumour progression by regulating invasion, metastasis, tumour growth and angiogenesis ( Figure 1).…”
Section: Discussionsupporting
confidence: 89%
“…It has also been shown to regulate tumour progression in various carcinomas (Suwa et al, 1998;Clark et al, 2000;Kleer et al, 2002;Kondo et al, 2004). He et al (2008) showed that RhoC-siRNA (short-interfering RNA) reduced adhesion to Matrigel invasion and migration of SiHa cells. Studies indicate that a cross-talk exists between RhoC and other signalling molecules such as MAPK and vascular endothelial growth factor (Vegf).…”
mentioning
confidence: 99%
“…Moreover, it has been shown that expression of some Rho-GTPases and their regulatory proteins is altered in human cancers such as prostate, colon, lung, and breast cancer [18]. Cell culture experiments showed that RhoC regulates invasion and motility of cervical cancer cells [19,20]. Furthermore, it has been reported that RhoC is overexpressed in biopsies from squamous carcinoma of the cervix (SCC) and cervical intraepithelial neoplasia (CIN) II/III when compared to normal cervical epithelium and CIN I [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the RhoC gene was involved in the occurrence and development of liver cancer, and that a close association existed between the high expression of RhoC and the phenotype of hepatocellular carcinoma regarding cell invasion and metastasis (38). Previous studies demonstrated that RhoA/C was highly expressed in a variety of malignancies, participated in the adhesion and migration of tumor cells, and markedly promoted the occurrence and development of tumors (39)(40)(41)(42). As a novel tumor marker, Rho can be applied to distinguish between benign and malignant lesions, and may help to assess the ability of tumor metastasis and prognosis (43).…”
Section: Discussionmentioning
confidence: 99%